La1.7Ca0.3Ni0.75Cu0.25O4‐δ‐Layered Perovskite as Cathode on La0.9Sr0.1Ga0.8Mg0.2O3 or Ce0.8Gd0.2O2 Electrolyte for Intermediate Temperature Solid Oxide Fuel Cells. Issue 2 (18th January 2016) - Myung, Jae‐ha; Shin, Tae Ho; Huang, Xiubing; Savaniu, Cristian; Irvine, John
Abstract : La2 NiO4+δ ‐based oxides, mixed ionic–electronic conductors with K2 NiF4 ‐type structure, have been considerably investigated in recent decades as electrode materials for advanced solid oxide fuel cells (SOFCs) due to their high electrical conductivity and oxidation reduction reaction (ORR) activity. In this study, La1.7 Ca0.3 Ni0.75 Cu0.25 O4+δ was investigated as a potential cathode on La0.9 Sr0.1 Ga0.8 Mg0.2 O3 electrolyte support. Furthermore, La1.7 Ca0.3 Ni0.75 Cu0.25 O4+δ was examined on thin Ce0.8 Gd0.2 O2 (GDC) electrolyte with Ni‐GDC anode support for intermediate temperature SOFCs (IT‐SOFCs). La1.7 Ca0.3 Ni0.75 Cu0.25 O4‐δ cathode with gadolinium doped ceria (GDC) electrolyte and NiO‐GDC anode support showed a maximum power density of 0.75 W/cm 2 in H2 and lower polarization resistance, Rp (<0.1 Ω cm 2 ), in impedance spectroscopy at 700°C.